Mapping of fisheries centers in West Aceh Regency based on the distribution of fishing infrastructure - Fachrurozi Amir; Erfan Erfan; Fardian Fardian; Fajar Nuansa; Ridha Dwiriansyah; Rosmalinda Rosmalinda; Tania Mauliza; Zulfahmi Zulfahmi; Afdhal Fuadi (Jurnal Perikanan Terpadu, 2025)
The availability of fisheries infrastructure data in an area is the first step in improving and enhancing the management of the fisheries system, because the existence of fisheries infrastructure is an inseparable part in supporting the success of fishing activities. With accurate infrastructure data, it can be used as a reference in planning the development of marine and fisheries centers. In West Aceh Regency, there are currently many marine and fisheries infrastructures, but no research has been conducted on mapping fisheries centers based on the distribution of existing fisheries infrastructure. The absence of updated infrastructure data is worried to have an impact on the optimization of marine and fisheries resource management. The purpose of this study is to map fisheries centers based on the distribution of fisheries infrastructure. The method used in this study is the survey method, where data collection in the field was carried out in three sub-districts that directly border the coastal area, namely Samatiga District, Johan Pahlawan District and Meureubo District. The infrastructure coordinates obtained from the field will be processed and presented in the form of a map using the ArcGIS application. The results of the study showed that in West Aceh Regency there are 1 PPI and 6 TPI, 31 infrastructure for procurement and repair of fishing vessels, and 9 infrastructures before and  after fishing. The fisheries center in Samatiga District is in the Kuala Bubon area, the fisheries center in Johan Pahlawan District is along the Krueng Cangkoi estuary river, while the fisheries center in Meureubo District is in one of the rivers in Gampong Meureubo and Gampong Ujong Drien.